Case referrals to A.I.I.S.H. - V, Uma (Journal of All India Institute of Speech and Hearing, 1972)
Until the First World War, it was not evident to the Otologists that functionally deaf patients could exists. It has only been since World War I, when relatively large number of psychogenically deaf patients were reported by the Military rural rehabilitation centres, that the suspicion or similar conditions existing in civilian population arose